2012
DOI: 10.1371/journal.pone.0033557
|View full text |Cite
|
Sign up to set email alerts
|

The Peritoneum as a Natural Scaffold for Vascular Regeneration

Abstract: Objective The peritoneum has the same developmental origin as blood vessels, is highly reactive and poorly thrombogenic. We hypothesize that parietal peritoneum can sustain development and regeneration of new vessels. Methods and Results The study comprised two experimental approaches. First, to test surgical feasibility and efficacy of the peritoneal vascular autograft, we set up an autologous transplantation procedure in pigs, where a tubularized parietal peritoneal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Moreover, in contrast to Bonvini et al[21] who showed the need of an external tutor to a tubularized autologous nondecellularized PPt to promote acquisition of an arterial phenotype, the tubularized DPPt in our study showed acquisition of an arterial phenotype and no aneurysm appearance without the need of tutor. This observation suggests the superiority of our DPPt to autologous PPt for cardiovascular reconstruction in the pig.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in contrast to Bonvini et al[21] who showed the need of an external tutor to a tubularized autologous nondecellularized PPt to promote acquisition of an arterial phenotype, the tubularized DPPt in our study showed acquisition of an arterial phenotype and no aneurysm appearance without the need of tutor. This observation suggests the superiority of our DPPt to autologous PPt for cardiovascular reconstruction in the pig.…”
Section: Discussioncontrasting
confidence: 99%
“…These include mechanical cues, biochemical cues (incorporation of native ECM (extracellular matrix), protein binding, etc.) and bioelectric cues (electrical stimulation) [2][3][4][5][6][7][8][9][10][11]. Electrospinning is an exciting avenue that allows for a wide range of scaffold morphologies to be created [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…38 Bonvini et al Observed that the parietal peritoneum acts as a scaffold to support blood vessel regeneration. 39 In other experimental animal studies, complete endothelialization of peritoneal grafts was observed as early as 2 weeks after implantation. 40,41 Chin et al first described the use of FAP for partial IVC reconstruction in 6 patients in 1999 and later in 22 complete IVC reconstructions, with no reported complications.…”
Section: Inferior Vena Cava Reconstruction With Autologous Peritoneummentioning
confidence: 89%